2017
DOI: 10.3892/ijmm.2017.3348
|View full text |Cite
|
Sign up to set email alerts
|

Genome expression profiling predicts the molecular mechanism of peripheral myelination

Abstract: The present study aimed to explore the molecular mechanism of myelination in the peripheral nervous system (PNS) based on genome expression profiles. Microarray data (GSE60345) was acquired from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) were integrated and subsequently subjected to pathway and term enrichment analysis. A protein-protein interaction network was constructed and the top 200 DEGs according to their degree value were further subjected to pathway enrichment analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…KEGG and GSEA analysis identified several common pathways and DEGs, such as oocyte meiosis and the proteasome. The down-regulation of oocyte meiosis showed that the proliferation of Schwann cells decreased after bone marrow formation [38]. In the present study, we found that oocyte meiosis was enriched when the expression of SC markers increased; this finding concurred with the previous literature.…”
Section: Discussionsupporting
confidence: 93%
“…KEGG and GSEA analysis identified several common pathways and DEGs, such as oocyte meiosis and the proteasome. The down-regulation of oocyte meiosis showed that the proliferation of Schwann cells decreased after bone marrow formation [38]. In the present study, we found that oocyte meiosis was enriched when the expression of SC markers increased; this finding concurred with the previous literature.…”
Section: Discussionsupporting
confidence: 93%
“…In Multiple System Atrophy, miRNA-339-5p was specifically downregulated ( Su et al, 2022 ). MiR-339-5p has been linked to the NF-B and p53 signaling pathways, both of which are important for peripheral myelination ( Wu, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… 40 The search updated in November 24, 2021 and the search term was set as “sepsis.” The inconsistent gene IDs of different resources were manually inspected and converted into Official Gene Symbols. In reference to the previous study, 41 the top 200 DEGs (top 100 upregulated and top 100 downregulated genes), as representatives of highly variable genes, were selected as sepsis‐associated genes. In addition, a portion of 156 core genes picked from sepsis‐related module in the section of WGCNA was also included.…”
Section: Methodsmentioning
confidence: 99%